Coating delamination analysis of diamond/Ti and diamond/Ti-6Al-4V systems using cohesive damage and extended finite element modeling. (2nd September 2021) - Zain-ul-Abdein, Muhammad; Ahmed, Furqan; Durst, Karsten; Ali, Mohsin; Daraz, Umar; Khan, Ammar A
Abstract: Diamond coatings are known to improve the wear resistance properties of substrate materials. This paper aims at analyzing damage behavior of brittle diamond coating deposited on two different ductile substrates, namely pure-Ti and Ti-6Al-4V alloy, subjected to uniaxial tensile loading. In-situ tensile tests were conducted on diamond/Ti and diamond/Ti-6Al-4V coated samples to identify the stress-strain response and the damage behavior of the coating. Surface imaging was performed using scanning electron microscope (SEM). The cross sections were made with the focused ion beam (FIB) gun installed in SEM to observe the coating failure modes. Energy dispersive x-ray and x-ray diffraction analyses were carried out to determine composition. The SEM analysis revealed micro-crystalline morphology of the coating and FIB cross-sections showed diamond coating top-layer, TiC interlayer and substrate at the bottom. The XRD and EDX findings confirmed the regions observed in FIB cross-section via chemical analysis. The in situ tensile tests revealed that the coating had undergone failure through crack initiation, fragmentation and delamination. The bucking of the coating under transverse compressive strain of the substrate was also observed. The Ti-6Al-4V alloy caused early cracking and delamination of the coating owing to its higher yield strength and higher rate of stress transfer to the coating. Two-dimensional finite element models were developed to simulate various damage modes, such as cracking, buckling and delamination. Extended finite element method and cohesive damage modeling were exploited to observe cracking and buckling, respectively. Numerical results revealed that the coating was more prone to failure when Ti-6Al-4V, a high yielding less ductile, substrate was used instead of a low yielding highly ductile Ti substrate. Moreover, buckling was found to be the major reason of delamination than bulk cracking. The coating is, therefore, likely to delaminate more severely under the compressive (buckling) than the tensile (bulk cracking) mode of deformation.